2020
DOI: 10.1007/s10008-020-04809-6
|View full text |Cite
|
Sign up to set email alerts
|

Cation exchange behavior during the redox switching of poly (3,4-ethylenedioxythiophene) films

Abstract: Poly (3,4-ethylenedioxythiophene), PEDOT, films were synthesized at room temperature by potentiodynamic and potentiostatic step deposition in aqueous solutions containing EDOT monomer and LiClO4. In some solutions, the effect of small amounts of sodium dodecylsulfate, SDS, on the polymerization rate of EDOT and on the stiffness of the obtained PEDOT film was studied. The obtained PEDOT films were transferred in aqueous solutions containing cations with different molar mass, such as H+, Li+, Na+, K+, and Cs+. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…PSSis a polyanion and is sterically hindered once it is incorporated within the polymer blend, while a small ion like Clcan move more freely. [57] Since both anions are highly soluble in water we utilized aqueous polymerization.…”
Section: Influence Of Solvent Counterion and Electropolymerization Mo...mentioning
confidence: 99%
“…PSSis a polyanion and is sterically hindered once it is incorporated within the polymer blend, while a small ion like Clcan move more freely. [57] Since both anions are highly soluble in water we utilized aqueous polymerization.…”
Section: Influence Of Solvent Counterion and Electropolymerization Mo...mentioning
confidence: 99%
“…PSSis a polyanion and is sterically hindered once it is incorporated within the polymer blend while a small ion like Clcan move more freely. [47] Since both anions are highly soluble in water we utilized aqueous polymerization.…”
Section: Influence Of Solvent Counterion and Electropolymerization Mo...mentioning
confidence: 99%
“…It has been reported that cations can be trapped in the polymer layer during the cycling of a similar PEDOT/sodium dodecylsulfate blend system. [47] Thus, the larger size of Ni 2+ (than Na + ) may have prevented its efficient removal during desorption. It is worth noting that the current plateau is reached early within the experiment time frame in chronoamperograms of electroadsorption and electrodesorption experiments (Figure S11a).…”
Section: Complete Esix Swing Of Pedot/pss Coated Carbon Papers For Ni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting polymers such as polyaniline and its derivatives (Qu et al 2020), polythiophene (Bazzaoui et al 1994), polypyrrole (Omastová and Mičušík 2012), and poly(3,4-ethylenedioxythiophene) (Gruia et al 2020) are used in a number of fields in industry such as corrosion protection of metals (Sazou and Deshpande 2017), conducting textiles (Tseghai et al 2020), biosensors and gas sensors (Yin et al 2006), electrocatalysis (Gustafson et al 2014), electrochromic display devices (Tian et al 2017), supercapacitors (Deshpande et al 2013), and in rechargeable batteries (Hong et al 2020). This is due to their excellent features such as low cost, environmental stability, light weight, and good electrical properties.…”
Section: Introductionmentioning
confidence: 99%